Power loss in dipping internal reflectors, imaged using ice-penetrating radar. Issue 67 (2014) - Holschuh, Nicholas; Christianson, Knut; Anandakrishnan, Sridhar
Abstract: The geometry of ice-sheet internal layers is frequently interpreted as an indicator of present and past ice-sheet flow dynamics. One of the primary goals of radio-echo sounding is to accurately reproduce that layer geometry. Internal layers show a loss in reflection amplitude as a function of increasing dip angle. We posit that this energy loss occurs via several mechanisms: destructive interference in trace stacking, energy dispersion through synthetic aperture radar (SAR) processing and off-nadir ray path losses. Adjacent traces collected over a dipping horizon contain reflection arrivals which are not in phase. Stacking these traces results in destructive interference. When the phase shift between adjacent traces exceeds one-half wavelength, SAR processing, which otherwise coherently combines data from dipping reflectors, disperses the energy, reducing image quality further. Along with amplitude loss from destructive stacking and SAR dispersion, imaging reflectors from off-nadir angles results in additional travel time and thus additional englacial attenuation relative to horizontal reflectors at similar depths. When selecting radar frequency, spatial sample rate and stacking interval for a given survey, the geometry of the imaging target must be considered. Based on our analysis, we make survey design recommendations for these parameters.